Heavier loads in flywheel exercise induce greater post-activation performance enhancement in countermovement jumps compared to heavy Smith machine squats in males - Shi, Jianhua; Yan, Bing; Yu, Mengjie; Wang, Zhe; Wang, Yang; Liu, Haoyang; Zhang, Wei; Girard, Olivier (Biology of Sport, 2024)
We evaluated the effects of post-activation performance enhancement through flywheel exercise with varying inertial loads compared to traditional resistance exercise on countermovement jump performance and muscle recruitment. In a randomized crossover design, 13 trained men completed four main experimental trials after three familiarization sessions. These conditions included a traditional trial consisting of 5 sets of 1 repetition using the Smith machine (SM) squat at 90% 1RM, and three flywheel ergometer trials. Each flywheel protocol consisted of 3 sets of 8 repetitions with 3-minute rest intervals between sets, utilizing one of three inertial loads (0.0465, 0.0784, and 0.1568 kg · m 2 for light, moderate, and heavy, respectively). Participants performed countermovement jumps before (baseline), immediately after (0 minute), and at the fourth (+4 minutes), eighth (+8 minutes), and twelfth (+12 minutes) minute following exercise. Compared to baseline, jump height was higher at +4 minutes for SM squats ( p = 0.009). All flywheel conditions exhibited higher jump heights at +4 minutes ( p < 0.05), +8 minutes ( p < 0.001), and +12 minutes ( p < 0.001) compared to baseline. Additionally, moderate and heavy loads resulted in higher jump heights at 0 minute (both p < 0.001). Integrated electromyographic activity values, a proxy for muscle recruitment, were significantly higher for the gluteus maximus muscle at both +8 minutes and +12 minutes for moderate (both p = 0.004) and heavy loads ( p ≤ 0.002) compared to SM squats. Overall, flywheel protocols produce greater post-activation performance enhancement, extend the time window for improvement, and recruit more active musculature compared to heavy-load SM squats, particularly with heavier loads acting as a stronger preload stimulus.